Morphine for the Treatment of Pain in Sickle Cell Disease - Mihir Gupta; Lilian Msambichaka; Samir K. Ballas; Kalpna Gupta (The Scientific World Journal)
Pain is a hallmark of sickle cell disease (SCD) and its treatment remains challenging. Opioids are the major family of analgesics that are commonly used for treating severe pain. However, these are not always effective and are associated with the liabilities of their own. The pharmacology and multiorgan side effects of opioids are rapidly emerging areas of investigation, but there remains a scarcity of clinical studies. Due to opioid-induced endothelial-, mast cell-, renal mesangial-, and epithelial-cell-specific effects and proinflammatory as well as growth influencing signaling, it is likely that when used for analgesia, opioids may have organ specific pathological effects. Experimental and clinical studies, even though extremely few, suggest that opioids may exacerbate existent organ damage and also stimulate pathologies of their own. Because of the recurrent and/or chronic use of large doses of opioids in SCD, it is critical to evaluate the role and contribution of opioids in many complications of SCD. The aim of this review is to initiate inquiry to develop strategies that may prevent the inadvertent effect of opioids on organ function in SCD, should it occur, without compromising analgesia.